Polypeptides Targeting Paracoccidioides brasiliensis Drk1 - Marcos, Caroline Maria [UNESP]; de Oliveira, Haroldo Cesar [UNESP]; Assato, Patricia Akemi [UNESP]; de Oliveira, Lariane Teodoro [UNESP]; Fregonezi, Nathália [UNESP]; dos Santos, Kelvin Sousa [UNESP]; Costa-Orlandi, Caroline Barcelos [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (MDPI, 2023)
Considering the toxicity of conventional therapeutic approaches and the importance of precise mechanistic targets, it is important to explore signaling pathways implicated in fungal pathobiology. Moreover, treatment of paracoccidioidomycosis, a systemic mycosis caused by a dimorphic fungus, requires prolonged therapeutic regimens. Among the numerous factors underpinning the establishment of Paracoccidioides spp. infection, the capacity to transition from the mycelial to the yeast form is of pivotal importance. The Drk1 protein of Paracoccidioides brasiliensis likely plays a decisive role in this morphological shift and subsequent virulence. We identified peptides with affinity for the PbDrk1 protein using the phage-display method and assessed the effects of these peptides on P. brasiliensis. The peptides were found to inhibit the phase transition of P. brasiliensis. Furthermore, a substantial proportion of these peptides prevented adhesion to pneumocytes. Although these peptides may not possess inherent antifungal properties, they can augment the effects of certain antifungal agents. Notably, the cell wall architecture of P. brasiliensis appears to be modulated by peptide intervention, resulting in a reduced abundance of glycosylated proteins and lipids. These peptides were also evaluated for their efficacy in a Galleria mellonella model and shown to contribute to enhanced larval survival rates. The role of PbDrk1, which is notably absent in mammals, should be further investigated to improve the understanding of its functional role in P. brasiliensis, which may be helpful for designing novel therapeutic modalities.
Keywords: Drk1; Paracoccidioides brasiliensis; peptides; phage-display